Effects of laser scanning speed on surface roughness and mechanical properties of aluminum/Polylactic Acid (Al/PLA) composites parts fabricated by fused deposition modeling. (November 2020) - Zhang, Xinzhou; Chen, Lan
Abstract: Although fused deposition modeling (FDM) has gradually become one of the popular additive manufacturing technologies in different industries, high surface roughness has always been an inevitable disadvantage of FDM parts. Laser polishing represents a recent and novel application of laser surface irradiation that can be used for precise, post-process smoothing of the rough surfaces commonly encountered on FDM parts. The influence of laser polishing on surface modification and mechanical properties of aluminum/Polylactic Acid (Al/PLA) composites has been investigated. Laser scanning speed was varied to evaluate its effect on the surface quality and mechanical properties of the experimental samples. The results indicated that laser polishing could enable reductions in surface roughness of over 86.6% (from 23.27 μm to 3.11 μm Sa ). The tensile strength of specimen also increased from 41.01 MPa to 51.31 MPa with increasement of 25.1%. The dynamic mechanical analysis (DMA) results showed that there was a remarkable improvement in the storage modulus and glass transition temperature of Al/PLA composite specimens after laser polishing, which suggested that the laser polishing treatment could play a role in decreasing the porosity inside the FDM parts and improve interfacial adhesion between the PLA matrix and Al fibers. Moreover, the fracture morphologies were observed to investigate the possible strengthening mechanism. These results demonstrate how laser polishing can simultaneously smooth and modify the surface characteristics of a FDM part surface. Graphical abstract: Image 1 Highlights: Laser polished additive manufactured Al/PLA has higher surface quality and many defects are removed. A maximum reduction in Al/PLA surface roughness is achieved at optimized polishing settings (laser scan speed of 100 mm/s). Laser polishing effectively improves the dynamic mechanical properties and tensile properties of the FMD Al/PLA. After laser polishing treated, Al/PLA composite specimens had a higher storage modulus and glass transition temperature. The strengthening mechanism induced by laser polishing is analyzed.